Analisis Kepemimpinan dan Motivasi terhadap Kinerja Pegawai pada Kantor Penanaman Modal dan Pelayanan Terpadu Kabupaten Agam - Syaleh, Hariman (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2017)
This study aims to see "Analysis of leadership and motivation on the performance of employees at the investment office and integrated services Agam District". The number of population and sample in this research all employees at integrated investment office and service of Agam Regency through the spreading of questionnaire with likert scale model then tested to validan and reliability of the questionnaire. Data analysis technique used is the method of Multiple Linear Regression Analysis, after passing the classical assumption test using SPSS program. In this study leadership (X1) and motivation (X2) as independent variables, performance (Y) as the dependent variable. The result of this research is a). Leadership has positive and significant effect there is employee performance that is equal to 0,222 with significance level 0,026 <0,05. b). Motivation have positive and significant effect there is employee performance that is equal to 0,782 with significance level 0,000 <0,05, leadership and motivation together have positive significant effect to employee performance equal to 51,623 with significance level 0,000 <0,05. Based on the conclusions obtained then it is suggested to the next researcher, if you want to do a similar research is expected to add other factors that can affect the performance of employees such as incentives, work environment, and others.